Dinamika Pertumbuhan dan Strategi Daya Saing di Sentra Produksi Tembakau Jawa Timur - Nadhirah, Aulia; Saadillah, Dinu; Al Ardi, Aditya Nizar; Hardiyani, Rini (Universitas Galuh, 2025)
This study aims to analyze the dynamics of growth and competitiveness strategies in four main centers of tobacco production in East Java, namely: Jember Regency, Probolinggo Regency, Pamekasan Regency and Bojonegoro Regency. This study uses a compound annual growth rate (CAGR) analysis approach to production, harvested area and productivity in 2013 to 2023. The results of the analysis show that all regencies experienced positive growth rates. Bojonegoro Regency and Pamekasan Regency received the highest production CAGR values, namely 18.99% and 18.52%, respectively. Jember Regency excelled in productivity CAGR value with a value of 11.84% and Probolinggo Regency experienced a decrease in harvested area CAGR value triggered by lack of access to technology and incoming information. When compared to the national level, the four regions showed better performance in all main indicators. These findings confirm that East Java has great potential as a center for national tobacco agribusiness growth. To strengthen competitiveness, recommended strategies include strengthening farmer-industry partnerships, product downstreaming, optimizing Tobacco Excise Revenue Sharing Funds (DBH-CHT), improving market governance, and implementing quality certification.